2018
DOI: 10.1002/jat.3742
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cadmium exposure induced hepatic cellular stress and inflammation in aged female mice

Abstract: Previous studies have revealed that acute cadmium (Cd) exposure led to inflammation in different organs through an oxidative stress mechanism. However, whether chronic Cd exposure induces inflammation in liver and the mechanistic link between inflammation and cell stress remains unclear. In the present study, we investigated the effects of chronic Cd exposure on hepatic cellular stress and inflammatory responses. Female CD1 mice were administrated with CdCl2 (10 and 100 mg/L) in drinking water for 57 weeks. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Cadmium (Cd) is an environmentally abundant toxic heavy metal (Abarikwu et al, 2018;Fan et al, 2018;Zhang et al, 2018). Food and cigarettes are two major sources of human exposure to Cd (Mannino et al, 2004;Ivanova et al, 2017); however, higher levels of exposure to Cd may be seen in occupational settings, such as nickel-cadmium battery manufacturing enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium (Cd) is an environmentally abundant toxic heavy metal (Abarikwu et al, 2018;Fan et al, 2018;Zhang et al, 2018). Food and cigarettes are two major sources of human exposure to Cd (Mannino et al, 2004;Ivanova et al, 2017); however, higher levels of exposure to Cd may be seen in occupational settings, such as nickel-cadmium battery manufacturing enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…It is partly because there is a large number of metallothionein in these organs, which is easy to bind with heavy metals such as Cd [27]. The toxicity to liver and/or kidneys of mice induced by Cd has been reported in previous studies, which is specifically manifested in liver and kidney dysfunction, oxidative stress and pathological changes [28][29][30][31]. Ca is known as an essential element that is of significance in whole-body growth [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cd is highly toxic and non-biodegradable and has a half-life of 10–30 years [ 11 ]. Numerous studies have indicated that environmental Cd exposure causes damage of multiple organs, including testicles, liver, kidney, bones and lungs [ [12] , [13] , [14] , [15] , [16] ]. Indeed, kidney is a major accumulation organ of Cd, and former studies have shown that chronic exposure to cadmium can trigger renal dysfunction [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%